Bullying : Masalah yang Berdampak Terhadap “Suicide Ideation” - Dina Dwiyanti; Silvia Rohmatila Putri; Eny Winaryati (Universitas Muhammadiyah Semarang, 2022)
This study aims to examine the role of bullying on suicidal ideation or suicidal ideation in college students. Researchers used quantitative techniques using questionnaires distributed online. The subjects in this study were students and active students aged 18-23 years. Most of the respondents alreadyunderstand about bullying, except for the type of relational bullying. The type of bullying that most respondents experienced was verbal bullying. The impacts of bullying include causing a person to feel worthless, feeling sorry for being born, and depression that triggers suicidal ideation. There is norelationship between bullying and suicide ideation. Significant but obtained a percentage of 4.4% and the rest is influenced by other factors.Keywords: bullying, suicide ideation, student